(untitled) (Global Journal of Human-Social Science, 2017)
The objective of this paper is to conduct an analytical exercise on dysfunctions observed in the formulation and implementation of public policies of the media in relation to the gender issue Despite the efforts made by Morocco to include the gender dimension in public media policies the situation of women in the media landscape remains precarious Whether at the level of the exercise of media-related businesses the engagement in the media programs or access to positions of responsibility Moroccan women are very poorly represented Even more surprising the media contribute to widen the gap between the actual value of Moroccan women and the image that one has of herself Morocco is a long way to go before all the legitimate aspirations of women are reached